1994
DOI: 10.1111/j.1440-1819.1994.tb03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating Attitudes Test in Japan

Abstract: A Japanese version of the Eating Attitudes Test (EAT) was developed and validated using a group of anorectics and Japanese female controls. Its sensitivity was considered to be low for anorectics, especially for the fasting type anorectics. A cross-cultural comparison of the EAT scores of anorectics showed some significant differences among those found in Japan, Canada and Germany. A survey of eating disorders among 286 Japanese female students was carried out with a Japanese EAT. Three cases of bulimia nervos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Respondents are asked to rate each item according to the past seven days. The reliability and validity of each Japanese version has already been confirmed (Doi, Roberts, Takeuchi, & Suzuki, 2001; Ujiie & Kono, 1994; Someya et al., 2001; Kitamura & Suzuki, 1993; Asukai et al., 2002).…”
mentioning
confidence: 83%
“…Respondents are asked to rate each item according to the past seven days. The reliability and validity of each Japanese version has already been confirmed (Doi, Roberts, Takeuchi, & Suzuki, 2001; Ujiie & Kono, 1994; Someya et al., 2001; Kitamura & Suzuki, 1993; Asukai et al., 2002).…”
mentioning
confidence: 83%
“…The development of the items was based on clinical descriptions of AN phenomenology and criteria provided by Feighner, et al (1972) to diagnose this eating disorder (ED). Over time, the EAT has became one of the most broadly used self-reports in the field of ED in a variety of cultures (Castro, Toro, Salamero, & Guimera, 1991;De Leon, Ruiz, & Camacho, 2008;Koslowsky, et al, 1992;Leichner, Steiger, Puentes-Neuman, Perreault, & Gottheil, 1994;Nasser, 1986Nasser, , 1997Neumaerker, Dudeck, Vollrath, & Neumaerker, 1992;Pereira, et al, 2008;Ranzenhofer, et al, 2008;Ujiie, & Kono, 1994).…”
mentioning
confidence: 99%
“…Denying symptoms of eating disorder behaviour and attitudes is in part immanent to anorexia and, in order to overcome this problem and to improve case detections, the authors proposed the inclusion of further questions concerning weight and mood. Ujiie and Kono [3] pointed out high false-negative mean scores among the restricting type of anorexia. Mintz and O'Halloran [1] reached a similar result and suggested that the EAT may not be a valid assessment tool for the restricting type.…”
Section: Introductionmentioning
confidence: 99%